How Dentists Face the COVID-19 in Mexico: A Nationwide Cross-Sectional Study - Casillas Santana, Miguel Ángel (Int J Environ Res Public Health, 2021)
Background: on 7 January 2020, a new type of coronavirus was isolated, the Severe Acute Respiratory Syndrome Coronavirus2 (SARS-CoV-2), the organism causing the outbreak that has affected the lives of all humans and has modified the rules of coexistence around the world. In Mexico, from 3 January 2020 to 9 January 2021, there have been 1439, 569 confirmed cases of COVID-19 with 131,031 deaths. The World Health Organization reported that Mexico was ranked twelfth, in terms of confirmed cases of COVID-19 by country. Aim: the objective of this study was to determine what modifications dentists from the Mexican Republic have made to their dental practice during theCOVID-19 pandemic. Methods: the study was conducted based on a questionnaire to evaluate the dentists’ response and knowledge on the modifications in their dental practice to combat the new coronavirus’s cross-transmission. The questionnaire was piloted before it was distributed. The questionnaire was disseminated through the social network Facebook. The questionnaire was distributed to groups of dentists on Facebook, in each of the Mexican Republic states. The survey was carried out during June 2020. Results and Conclusions: from the 32 states of the Mexican Republic, 29 participated with at least one respondent. The results of the applied survey suggest that dentists, at least the population of surveyed ones, have proper knowledge of detection methods of patients suspected of COVID-19, preventive measures that must be applied in the dental office to decrease the risk of infection, and the appropriate procedures and solutions for dental office disinfection.